2018
DOI: 10.1021/jacs.8b03659
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Out-of-Plane Conductivity and Photovoltaic Performance in n = 1 Layered Perovskites through Organic Cation Design

Abstract: Layered perovskites with the formula (R-NH)PbI have excellent environmental stability but poor photovoltaic function due to the preferential orientation of the semiconducting layer parallel to the substrate and the typically insulating nature of the R-NH cation. Here, we report a series of these n = 1 layered perovskites with the form (aromatic- O-linker-NH)PbI where the aromatic moiety is naphthalene, pyrene, or perylene and the linker is ethyl, propyl, or butyl. These materials achieve enhanced conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
409
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(420 citation statements)
references
References 34 publications
10
409
1
Order By: Relevance
“…Pyrene‐CH 2 −NH 3 + has been used as an emitting chromophore in chloride, bromide and iodide based 2D layered hybrid perovskites . In the recent work of Passarelli et al., pyrene derivatives (pyrene‐O−C n H 2n −NH 3 + ) were used in 2D layered perovskites to improve the out‐of‐plane conductivity of these materials. In literature, there is a move away from the use of ‘simple’ alkylic (e. g. butylammonium) or benzylic (e. g. phenethylammonium) cations towards more complex cations with more extended π‐systems .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Pyrene‐CH 2 −NH 3 + has been used as an emitting chromophore in chloride, bromide and iodide based 2D layered hybrid perovskites . In the recent work of Passarelli et al., pyrene derivatives (pyrene‐O−C n H 2n −NH 3 + ) were used in 2D layered perovskites to improve the out‐of‐plane conductivity of these materials. In literature, there is a move away from the use of ‘simple’ alkylic (e. g. butylammonium) or benzylic (e. g. phenethylammonium) cations towards more complex cations with more extended π‐systems .…”
Section: Figurementioning
confidence: 99%
“…In the recent work of Passarelli et al., pyrene derivatives (pyrene‐O−C n H 2n −NH 3 + ) were used in 2D layered perovskites to improve the out‐of‐plane conductivity of these materials. In literature, there is a move away from the use of ‘simple’ alkylic (e. g. butylammonium) or benzylic (e. g. phenethylammonium) cations towards more complex cations with more extended π‐systems . We use a pyrene derivative as an example of such a type of molecule.…”
Section: Figurementioning
confidence: 99%
“…Importantly, the process of conductivity changed with temperature is reversible, the conductivity is reduced when the temperature is lowered (Figure S13). In previous work, researchers have tried to tune the conductivity of perovskite via changing the organic moieties, and obtained conductivity change can only cover no more than four orders of magnitude . In comparison, the conductivity change of (BED) 2 CuCl 6 spans close to six orders of magnitude, which is the highest value for perovskite materials.…”
Section: Figurementioning
confidence: 99%
“…In 2D perovskites, the organic cations are considered as insulating groups between the conductive inorganic layers . The activation energy for charge transport in 2D hybrid perovskites is affected by the distance of two adjacent inorganic layers . From single crystal structure (Figure S15), the distance between adjacent inorganic layers of these two crystals were 9.672 Å and 24.038 Å, respectively.…”
Section: Figurementioning
confidence: 99%
“…[24][25][26][27][28][29] In conclusion, we have demonstrated that the incorporation of conjugated diynes in 2D hybrid perovskites allows the thermally induced topochemical formation of polydiacetylenes in this class of materials.Unlike previous methods,the use of heat (instead of g-rays) as the polymerization inducer makes this ar ealistic option for its implementation in optoelectronic devices.W ehave also shown that it is possible to dope the formed polydiacetylenes inside the perovskites, which in turn leads to the formation of radicals and drastic improvement in light absorption and conductivity.T he incorporation of polymeric species in 2D perovskites can also have positive effects in the stability and mechanical properties of the materials,e ffects that will be studied in the near future.S imilarly,a ttempts to use these materials in optoelectronic devices and further studies to better understand the electronics properties,a nd to modulate the optical and electronic properties of these materials by means of controlled doping are underway in our laboratories. To the best of our knowledge,t he conductivities shown by 1-O 2 and 1-I 2 are the highest electrical conductivity reported for a2 Dp erovskite (n = 1) and are comparable to those reported for MAPbI 3 (MA = methylammonium).…”
Section: Angewandte Chemiementioning
confidence: 99%